Byron and marginality - Lennartz, Norbert (Edinburgh University Press, 2018)
This book approaches Byron from a completely new angle: no longer seen in terms of his status as a celebrity and a star on the book-selling market, Byron is instead seen as an outsider both in Regency society and, even more so, for his iconoclastic views of life and literature.